2016
DOI: 10.1021/jacs.6b07935
|View full text |Cite
|
Sign up to set email alerts
|

C2-Oxyanion Neighboring Group Participation: Transition State Structure for the Hydroxide-Promoted Hydrolysis of 4-Nitrophenyl α-d-Mannopyranoside

Abstract: The hydroxide-catalyzed hydrolysis of aryl 1,2-trans-glycosides proceeds through a mechanism involving neighboring group participation by a C2-oxyanion and rate-limiting formation of a 1,2-anhydro sugar (oxirane) intermediate. The transition state for the hydroxide-catalyzed hydrolysis of 4-nitrophenyl α-d-mannopyranoside in aqueous media has been studied by the use of multiple kinetic isotope effect (KIE) measurements in conjunction with ab initio theoretical methods. The experimental KIEs are C1-H (1.112 ± 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 62 publications
3
43
0
Order By: Relevance
“…This process has little biological precedent (for a related proposal see Ref. ), but occurs in the base‐promoted solvolysis of α‐mannosides …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This process has little biological precedent (for a related proposal see Ref. ), but occurs in the base‐promoted solvolysis of α‐mannosides …”
Section: Introductionmentioning
confidence: 99%
“…[11]), but occurs in the base-promoted solvolysis of a-mannosides. [12] Efforts to develop inhibitors of GH99 enzymes have relied upon appending 1,3-linked a-glucosyl (to target mammalian endo-a-1,2-mannosidases) or 1,3-linked a-mannosyl (to target bacterial endo-a-1,2-mannanases) groups to various sugarshapedh eterocycles. Spiro and co-workersr eportedt he discoveryo fa-glucosyl-1,3-deoxymannojirimycin (GlcDMJ) as an effective inhibitor of the mammalian enzyme, [13,14] and followon studies by Fleet and co-workersr evealed a-mannosyl-1,3deoxymannojirimycin (ManDMJ) to be as lightly weaker inhibitor for this enzyme ( Figure 1B).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25] Due to the noveltyo fo ur chemistry, am echanistic study was necessitated. [25] Due to the noveltyo fo ur chemistry, am echanistic study was necessitated.…”
Section: Resultsmentioning
confidence: 99%
“…8 Bennet et al reported computational analysis of formation of unprotected 1,2-anhdyro sugars from p-nitrophenyl glycosides. 9 Quite recently, the participation of a partially protected 1,2-anhydrofuranose was confirmed in a nucleoside synthesis. 10 However, in spite of the fact that unprotected 1,2-anhydro sugars possess potential utilities as a new donor substrate in the synthetic field of glycoscience, the direct experimental observation of totally unprotected 1,2-anhydro sugars has not been achieved yet.…”
mentioning
confidence: 97%